Plasmons as Sensors - Becker, Jan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Plasmons as Sensors covers the fundamental developments of plasmonic nanosenor design over the last few years. In his acclaimed thesis, Jan Becker addresses the relevant theoretical concepts and then applies these to discuss the properties and trends in nanoparticles of various shapes and sizes. The first discovery Jan makes in his PhD research is that there is an optimal shape for plasmonic nanoparticles used for sensing purposes. In further chapters he goes on to describe novel experimental methods to use plasmonic nanoparticles for molecular sensing. The approach he develops in parallel sensing is one which revolutionizes the field and allows investigation of a variety of topics from nanoparticle growth to membrane protein attachment. Many of the experiments described in this thesis have led to highly visible publications in international journals.
Light-Scattering and -Absorption of Nanoparticles -- Synthesis of Nanoparticles -- Analytical Methods -- Novel Setups -- Single Gold Nanoparticle Growth Monitored in situ -- Protein-Membrane Interaction -- The Optimal Aspect Ratio for Plasmonic Bio-Sensing -- Increasing Nanoparticles’ Refractive Index Sensitivity -- Plasmonic Focusing Reduces Ensemble Linewidth -- Self Calibrating Nano-Ruler.
Keywords: Nanochemistry; Nanotechnology; Biochemistry; Nanochemistry; Nanotechnology; Biochemistry, general